PRODUKTIVITAS BIOMASSA DAN ESTIMASI PRODUKTIVITAS ASTAXANTHIN MELALUI PEMODELAN KINETIK KULTUR CHLORELLA VULGARIS YANG DIBERI CEKAMAN FE2+ - Annafisah, Hamidah
Microalgae are micro-sized photosynthetic organisms that are currently widely used in various industries, one of which is for the production of astaxanthin. To increase the accumulation of astaxanthin, oxidative induction can be carried out such as the addition of Fe2+ to the cultivation medium. This study aims to estimate the productivity of astaxanthin in the microalgae Chlorella vulgaris biomass given oxidative Fe2+ induction through kinetic modeling. The direct effect of Fe2+ on growth was analyzed by administering Fe2+ with various concentrations of 0, 500, 750 and 1000 ?M at the end of the logarithmic phase. Meanwhile, to estimate the productivity of astaxanthin in C. vulgaris, the estimation parameters of the secondary data modeling results were used. The kinetic models used to estimate astaxanthin productivity include the logistic growth model, the medium nitrate consumption model and the Luedking-Piret product synthesis model. The results of the analysis show that the addition of Fe2+ concentration can increase biomass growth as indicated by the estimation results of the model parameters where the best growth is obtained at the addition of Fe2 + 500 ?M with the productivity values of biomass, Xmax and ?max respectively 0.065 g / L. day-1, 0.7242 g / L and 0.4707 day-1. Based on the estimation results using the Luedeking-Piret model from secondary data, the addition of Fe2 + concentration can increase the astaxanthin content in biomass. The highest estimation of astaxanthin content in C.vulgaris was obtained by adding Fe2 + 500 ?M of 30.16 mg / g with astaxanthin productivity of 1.68 mg / L. day-1. These results still need to be proven by further research due to differences in species and culture conditions with secondary data..